Variability of high jump kinematic parameters in longitudinal follow-up - Blazevic, I.; Antekolovic, L.; Mejovsek, M. (Kinesiology, 2006)
The aim of this research was to determine the basic kinematic parameters of the high jump as well as the impact of changes in kinematic parameters on the height of the jump, and finally to determine the variability of kinematic parameters in longitudinal research. By means of kinematic analysis 25 kinematic parameters were acquired for seven jumps performed in the time span of three years by an elite Croatian female high jumper. By analysis of the kinematic parameters and the height of the jump the parameters which correlated the most with the height of the jump were acquired. Those were: height of the flight of CG (H2), vertical velocity of CG at the end of the take-off (VVETO), height of the hips above the bar (HHIP), take-off angle (ANTO), take-off duration (DTO), angle at the moment of entering the take-off (ANETO), maximal height of CG at the moment of crossing the bar (CGMAX), horizontal velocity of CG in the penultimate stride in the run-up (HV2RU). The values of certain kinematic parameters increased with the increase in the height of the jump, while values of other kinematic parameters decreased with the increase in the height of the jump. Basic kinematic parameters that increased with the height of the jump were height of the flight of CG (H2), vertical velocity of CG at the end of the take-off (VVETO), height of the hips above the bar (HHIP), take-off angle (ANTO), maximal height of CG at the moment of crossing the bar (CGMAX) as well as horizontal velocity of CG in the penultimate stride in the run-up (HV2RU), while the values of kinematic parameters take-off duration (DTO) and angle at the moment of entering the take-off (ANETO) decreased with the increase in the height of the jump. By analyzing the kinematic parameters of all the observed jumps it was determined that all the parameters varied with the increase in the height of the jump. Parameters that had the highest variability with regard to the height of the jump were: length of the penultimate stride in the run-up (SD = 18.90), distance between CG and bar projection at the moment of the take-off leg positioning (SD = 15.24), distance between take-off point and the bar projection (SD = 11.78) and the length of the last stride during the run-up (SD = 11.11). The lowest variability was observed in the parameter take-off duration, which is the duration of contact between the take-off leg and the surface, indicated by the 0.007 value of standard deviation.